In search of Indonesian EFL learners` view of social presence in online learning: How do they perceive it? - Alfian, Alfian; Rozal, Edi; Berliana, Idea; Noprival, Noprival (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
Social presence is one of the key elements in developing a personal connection and encouraging collaboration, which supports meaningful learning in online learning. Understanding how students interpret social presence in online learning is crucial. This study aims to investigate how EFL learners at an Islamic institution perceive social interaction in online learning. This study also analyzes how male and female students view social interaction in online learning. Grounded in a quantitative approach, a Cross-sectional survey design was used in this study by distributing to a nine-item survey on the social presence questionnaire to one hundred thirty-one Islamic university EFL learners. The findings demonstrate that the EFL learners perceived social presence in online learning negatively. The result also shows that the perception of males and females differ significantly in which male students perceived that social interaction most likely occurs in online learning, whereas female students feel it was very little interaction. The findings of this research offer a crucial understanding of how EFL instructors might improve social presence in online learning